Pengaruh Jenis Ragi dan Lama Fermentasi terhadap Karakteristik Virgin Coconut Oil (VCO) - C.C. Kusuma, Yossinta; Mayun Permana, I Dewa Gde; Timur Ina, Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 1 (2022): Jurnal ITEPA, 2022)
Virgin coconut oil (VCO) is oil obtained from fresh old coconut and processed by squeezing with or without the addition of water, without heating or heating no more than 60oC and safe for consumption. This research was aimed for determining the effect of yeast type and fermentation time on the characteristics of virgin coconut oil and decided yeast type and fermentation time to produce the best characteristics of virgin coconut oil. The research based on a factorial Randomized block design (RBD) with the first factor was the type of yeast, namely bread yeast and tempeh yeast, and the second factor is the fermentation time, namely 24 hours, 36 hours, and 48 hours. Each combination treatment was replicated 3 times to obtain 18 experimental units. Data was analyzed using analysis of variance and if the treatment had a significant effect, its followed by the Duncan multiple range test (DMRT). The variables observed in this research were yield, moisture content, turbidity, free fatty acids (FFA), peroxide number, and flavor (hedonic and scoring). The results showed that interaction of yeast type and fermentation time had a significant effect (P<0.05) to yield and moisture content VCO. Types of bread yeast and tempeh yeast with 24 hours, 36 hours, and 48 hours of fermentation have a significant effect (p<0.05) on the aroma of VCO (hedonic and scoring). Type of tempeh yeast with a fermentation time of 36 hours for producing virgin coconut oil the best characteristics with yield 36.67%, moisture content 0.16%, turbidity 0.08%, free fatty acids 0.10%, peroxide number was not detected, coconut scent and liked.